Prospects and Options for Upgrading NSPP and Constituent Units into a National University of Public Administration - Hamid, Imran (Journal of Pakistan Administration, 2023)
This study reconnoiters the avenues of awarding a degree by NSPP after the completion of training programmers for civil servants. The objective of this research is to explore different prospects and options for upgrading NSPP and its constituent units into a National University of Public Administration. Instead of going into philosophical discussions on historical background of trainings of civil servants and their evolution as per needs of different eras, this study remains focused on the training regimes of civil servants in Pakistan since establishment of NSPP in 2005 and identification of practical steps which are required for upgrading NSPP into a degree awarding institute. This study primarily uses mixed method approach in answering the research question. This research presents a series of recommendations and considerations for policymakers and the management of NSPP about necessary steps to be taken including preparation and approval of well-thought-out charter, revamping of syllabi of different trainings to synchronize them with the course-work requirements of HEC, recruitment of faculty members with requisite qualification etc.
Keywords: university; public administration; bureaucracy; Constituent Units; Upgrading NSPP